Aesthetics of Human-AI Collaboration in Creative Activities : Art, Cultural Heritage, and Academic Research Practice - Szostak, Michał, (Schöningh, Fink and mentis Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2026)
The book explores the aesthetic insights into the transformative interplay between artificial intelligence and human creativity within art, cultural heritage, and academic research. It delves into how AI technologies reshape these areas, addressing both their potential to enhance creative processes and the challenges they present to traditional aesthetic frameworks of human creativity. Through a series of interdisciplinary chapters, the book examines applying AI-powered solutions in artistic endeavours, cultural heritage management, modern-day curation, and media content personalisation. It also explores how AI supports collaborative research and the modern translation profession, providing new aesthetic perspectives on beauty, truth, harmony, complexity, and trust in human-technology interactions. This book offers valuable insights for scholars, practitioners, and policymakers seeking to understand and navigate the evolving relationship between humans and AI.